Research on the impact of rural collective property rights system reform on rural industrial integration-the Yangtze River Economic Belt as an example - Long Zeng; Zhaoxuan Li (Frontiers in Sustainable Food Systems)
As a critical component of China’s rural reform, the rural collective property rights system reform offers substantial institutional support for advancing rural industrial integration by clarifying and delineating property rights. Utilizing panel data from 763 counties in the Yangtze River Economic Belt spanning 2012 to 2019, this study investigates the effects of rural collective property rights system reform on rural industrial integration, employing a multi-period difference-in-differences model as a quasi-natural experiment based on a pilot reform initiative. The findings indicate that, first, the rural collective property rights system reform significantly enhances rural industrial integration. This conclusion remains valid after robustness testing, confirming the causal relationship between the reform of the rural collective property rights system and the integration of rural industries, while also avoiding model estimation errors caused by sample selection bias and reverse causality. Second, the reform facilitates rural industrial integration by expanding the county-level market scale and elevating industrial agglomeration levels. Third, in the upper reaches of the Yangtze River Economic Belt, the reform significantly promotes rural industrial integration, whereas its effect is less pronounced in the middle and lower reaches; similarly, in major grain-producing areas with a stronger agricultural foundation, the reform markedly enhances rural industrial integration, though its impact is less evident in non-grain-producing regions. Fourth, rural collective property rights system reform has a significant promotional effect on the integration of rural industries in neighboring areas by enabling the sharing of technology, talent, and capital between regions.